The nutrient intake of children aged 12–36 months living in two communities in the Breede Valley, Western Cape province, South Africa - Tolulope A. Balogun; Martani J. Lombard; Mildred McLachlan (South African Family Practice)
Objective: The objective of this study was to describe the current macro- and micronutrient intake of children (both boys and girls) in two selected communities in the Breede Valley, Worcester.